The Effect of Job Training, Work Discipline and Career Development on Employee Performance at PT. Torpindo Concrete Galang - Riwa Rita Nababan; Melinda Siregar; Marthina Yunita Simanjuntak; Adika Fajar Putra; Suranta Josua Situmeang (PT FORMOSA CENDEKIA GLOBAL, 2023)
The existence of good management in an agency or company will be very supportive in the process of achieving company goals and building a company's economy or global economy. Therefore, the agency or government must conduct the selection of human resources strictly in order to achieve good performance. The research approach used by the author is quantitative research and qualitative descriptive research, and the nature of the research used is explanatory research. The conclusions obtained by the author are that simultaneously and partially variable job training (X1), work discipline (X2), and career development (X3) have a positive and significant effect on the performance of sdi employees and the pandemic sdi PT. Torpindo Galang Beton with a coefficient of determination value of s52%, which means that independent variables are able to increase the percentage of employee performance at PT. Torpindo Galang Concrete.